(3m-4n)^2+2(3m-4n)(3m+4n)-3(3m+4n)^2
1个回答
=9m^2-24mn+16n^3+18m^2-32n^2-27m^2-72mn-48n^2
=-96mn-64n^2
=-96*(-2)*1/4-64*(1/4)^2
=48-4
=44
相关问题
(m-2n)(2n+m)-(-3m-4n)(4n-3m)=
m+n/3-n-m/4=2 4m+n/3=14
{(m+n)/3-(n-m)/4=2 {4m+(n/3)=14 求m
如果m-3n+4=0 求(m-3n)^2+7m^3-3(2m^3n-m^2n-1)+3(m^3+2m^3n-m^2n+n
计算:[-m^3n/(m-n)^2]^4*[(n^2-mn)/m]^3/m^4n^10*[(mn-n^2)/m]^6
分式计算8m^2*n^4*(-3m/4n^3)(-m^2n/2)
[(m-n)^2*(m-n)^3]^2/(m-n)^4
{-3/2m+n=4 {2m+n=-3 求m,n 注意,
3m+2n/4=m+5n/-3=m-3n/5
[(m-n)^2*(n-m)^3]^2/(m-n)^4 [(-x^5)^2]^3/[(x^4)^2/(x^2)^3]